Pertumbuhan dan Produksi Tiga Varietas Sawi (Brassica juncea L.) dengan Sistem Hidroponik yang Berbeda (NFT, DFT, WICK) - Angga Febri Firmanzah; Endang Sri Wahyuni (JURNAL AGROPLANT, 2026)
This study aims to determine the growth and production of three varieties of mustard (Brassica juncea L.) with different hydroponic systems (NFT, DFT, Wick). This research was conducted in the JL greenhouse. Batu Raden Alley 01 No 01, Sumbersari District, Jember Regency. This study was conducted using a 3 x 3 factorial Complete Randomized Design (RAL) with 3 repeats. The first factor is the hydroponic system (S) which consists of 3 levels, S1 is the Nutrient Film Technique (NFT) system. S2 is a Deep Flow Technique (DFT) system. S3 is a Wick system. The second factor is the variety of mustard varieties (V) consisting of 3 levels, V1 is bitter mustard. V2 is a mustard white pakcoy. V3 is a mustard samhong king. The observational data were analyzed by F test (variance analysis) to determine the effect of treatment, using SPSS software, for windows version 26. The results showed that the NFT hydroponic system (S1) is the right hydroponic system for the growth and production of bitter mustard, chicory white pakcoy and Mustard samhong king shows the best growth and production, it can be seen paramater observing plant height, number of leaves, root length and fresh weight. The interaction of the best treatment is shown by the S1V3 treatment (NFT system, samhong king) which is shown by the parameters of plant height and fresh weight.